Double cholesterol inhibition — a new approach to effective control of hyperlipidemia and atherosclerosis - A. V. Susekov; N. B. Gornyakova; M. Yu. Zubareva; T. A. Rozhkova; E. Yu. Solovyeva (Кардиоваскулярная терапия и профилактика, 2009)
The increased level of low-density lipoprotein cholesterol (LDL-CH) is one of the risk factors (RFs) of coronary heart disease and atherosclerosis. Statins, with their vast evidence base on mortality reduction, are the principal medications in atherosclerosis treatment. The results of the recent controlled studies on CH reduction justified the decrease in target lipid levels: for LDL-CH — 2 mmol/l or less. Double CH inhibition is a new concept in plasma CH reduction by 50%, due to synthesis blockage (statins) and reduced intestinal reabsorption of dietary and biliary CH. The clinical trials of a fixed-dose combination Inegi ® (Ezetimibe / simvastatin) demonstrated its high effectiveness in achieving new target levels of LDL-CH, as well as good tolerability and safety, compared to statin monotherapy. The ongoing clinical trial IMPROVE-IT, assessing the effects of double CH inhibition on cardiovascular mortality, will clarify the role of Ezetimibe® and Inegi® in the treatment of dyslipidemia and atherosclerosis.